Portrait Stories - Ginsburg, Michal Peled, 1947- (Book collections on Project MUSE., 2015)
What makes stories about portraits so gripping and unsettling? 'Portrait Stories' argues that it is the ways they articulate the relation between subjectivity and representation. While in pre-19th century stories the portrait is presented as an unambiguous token of its subject's already established identity, the stories discussed in this book show subjectivity to be inseparable from representation. At the same time, portraiture highlights the way representation is inflected by particular interests and power relations, often determined by gender as well as class.